1994
DOI: 10.1203/00006450-199408000-00012
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral and Physiologic Effects of Nonnutritive Sucking during Gavage Feeding in Preterm Infants

Abstract: Behavioral and physiologic responsivity to nasogastric gavage feeding was assessed in 36 preterm infants on 2 consecutive d. On one of these days, a pacificr was provided during and after the gavage segment of the standardized protocol. The protocol was divided into segments that included baseline, preparatory handling, prcgavagc, gavage, and postgavage periods. Patterns of cardiac (heart period and vagal tone), oxygen saturation, behavioral state, and defensive behavioral responses to gavage were quantified. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
63
0
1

Year Published

2000
2000
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(67 citation statements)
references
References 12 publications
3
63
0
1
Order By: Relevance
“…Repeated exposure to patterned orocutaneous events, on the order of 12 to 24 min per day in the NICU presented simultaneous with NG tube feeds over the course of 7-10 days, provides the preterm infant with a neural entrainment experience that facilitates the development and strengthening of central pathways that regulate suck. Establishing the NNS provides the infant with additional benefits, including improved state control pre-feed [35][36][37][38][39] and post-feed, 40 growth, maturation, gastric motility, whereas decreasing stress 2,6,35,40,41 and enhancing oral feeds. 42 The present study has also demonstrated a significant positive relation between oral entrainment intervention and the transition to oral feed as taken from the infants' daily feed log.…”
Section: Discussionmentioning
confidence: 99%
“…Repeated exposure to patterned orocutaneous events, on the order of 12 to 24 min per day in the NICU presented simultaneous with NG tube feeds over the course of 7-10 days, provides the preterm infant with a neural entrainment experience that facilitates the development and strengthening of central pathways that regulate suck. Establishing the NNS provides the infant with additional benefits, including improved state control pre-feed [35][36][37][38][39] and post-feed, 40 growth, maturation, gastric motility, whereas decreasing stress 2,6,35,40,41 and enhancing oral feeds. 42 The present study has also demonstrated a significant positive relation between oral entrainment intervention and the transition to oral feed as taken from the infants' daily feed log.…”
Section: Discussionmentioning
confidence: 99%
“…31 Widstrom et al 28 found decreased somatostatin and increased gastrin levels in gastric aspirates of preterm infants that were allowed to suck on a pacifier during gavage feedings. Other studies have found that gastrin 20,31 and somatostatin 30 levels were not significantly altered in treatment and control groups.…”
Section: Development Of Nns and Related Factorsmentioning
confidence: 70%
“…23 In addition, these infants returned to a sleep state much faster. 20 One mechanism that has been postulated for the potential beneficial effect of NNS, that of improved weight gain, has been attributed to the optimal behavior states achieved with NNS. 24 General movements of the limbs, head, and trunk occur without a distinctive pattern or sequencing of the various body parts.…”
Section: Development Of Nns and Related Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…One postulated mechanism is a stimulation of digestive and anabolic hormones, although measurable hormonal differences have not been demonstrated. 169 Non-nutritive sucking with oral support 170 is associated with positive changes in behavior including enhanced physiologic stability, 171-173 a more alert and receptive behavioral state for feeds 174,175 and diminished signs of stress 176 and improved pain response. 177 Systematic reviews of experimental evidence for the practice of non-nutritive sucking have found a beneficial effect on length of stay and response to pain, but did not find consistent benefit involving behavioral states, sucking improvement, gastric emptying or weight gain.…”
Section: Role Of Sleep In Brain Developmentmentioning
confidence: 99%